History of Education in Cambodia: A Review of Literature From Past to Present - Sereyrath Em; Sarom Mok; Rany Sam; Ganda Febri Kurniawan; Dina Pen (istory Department, Faculty of Social Sciences, Universitas Negeri Semarang in collaboration with Masyarakat Sejarawan Indonesia (Indonesian Historical Society), 2025)
Abstract: From the beginning until now, education has been a significant factor in the Cambodian setting. The current article examines the origins of education in Cambodia, which dates back to the prehistoric period. Throughout Cambodian history, education has played a variety of meaningful roles. Education played a significant role in shaping the lives of individuals throughout the many eras of Cambodian prehistory and history. In prehistory, children learned by doing and observing the people around them. Education in Cambodia peaked during the Angkor Empire, also known as the Khmer Empire. During that period, hundreds of educational institutions were located across the country, including more advanced educational establishments in the city serving as Angkor's capital. Thousands of instructors were well-equipped to teach Khmer-speaking students. On the other hand, as the Angkor Empire collapsed, education in Cambodia gradually declined, a trend that persisted until the Khmer Rouge Regime finally eradicated education. During this period, the Khmer Rouge leaders targeted and killed the majority of instructors. Then the Cambodian government and other concerned education stakeholders have been working diligently to rebuild education in Cambodia since the end of that black period, and they have succeeded in doing so to the point where it is now. Finally, the article recommends that the concerned education stakeholders consider the past as the experiences for the present and improve the perspectives of future education. Abstrak: Sejak awal hingga sekarang, pendidikan telah menjadi faktor penting dalam tatanan Kamboja. Artikel ini membahas asal-usul pendidikan di Kamboja, yang dimulai sejak periode prasejarah. Sepanjang sejarah Kamboja, pendidikan telah memainkan berbagai peran yang berarti. Pendidikan memainkan peran penting dalam membentuk kehidupan individu di berbagai era prasejarah dan sejarah Kamboja. Pada masa prasejarah, anak-anak belajar dengan melakukan dan mengamati orang-orang di sekitar mereka. Pendidikan di Kamboja pernah mencapai puncaknya selama Kekaisaran Angkor, yang juga dikenal sebagai Kekaisaran Khmer. Selama periode tersebut, ratusan lembaga pendidikan berlokasi di seluruh negeri, termasuk lembaga pendidikan yang lebih maju di kota yang berfungsi sebagai ibu kota Angkor. Ribuan instruktur diperlengkapi dengan baik untuk mengajar siswa yang berbahasa Khmer. Di sisi lain, ketika Kekaisaran Angkor runtuh, pendidikan di Kamboja secara bertahap menurun, sebuah tren yang bertahan hingga Rezim Khmer Merah akhirnya memberantas pendidikan. Selama periode ini, para pemimpin Khmer Merah menargetkan dan membunuh sebagian besar instruktur. Pemerintah Kamboja dan pemangku kepentingan pendidikan lainnya telah bekerja keras untuk membangun kembali pendidikan di Kamboja sejak berakhirnya masa suram itu, dan mereka telah berhasil melakukannya hingga mencapai titik seperti sekarang. Terakhir, artikel ini merekomendasikan agar para pemangku kepentingan pendidikan mempertimbangkan masa lalu sebagai pengalaman untuk masa kini dan meningkatkan perspektif pendidikan di masa mendatang.